The elements in system analysis on principals’ managerial effectiveness in public secondary school - Isreal Chijiuka Oparaji; Martha-Rose Ifeoma Uwaezuoke; Eucharia Chinenye Okonkwo (S&Co Publishing, 2024)
The study which investigated the influence of system analysis on the principals’ managerial roles in public secondary schools in Imo State was aimed at identifying the elements of systems analysis and the factors bedeviling its utilization. The study was guided by two research questions and two hypotheses. The study adopted a descriptive research survey design. The population of the study comprised all the principals and teachers of public secondary schools numbering 268 and 5628 respectively. A random sampling technique was used to select 134 principals while a stratified random sampling technique was adopted to draw 563 teachers from the randomly selected schools which yielded a total of 697 participants. The instrument for data collection, the ‘Influence of Systems Analysis on Principals’ Managerial Effectiveness Questionnaire’ (ISAPME), was used to elicit information from the respondents. The validity of the instrument was certified through scholarly reviews. The internal consistency of the instrument was ascertained using the Pearson Moment Correlation Coefficient method which gave rise to the coefficient value of 0.84 which was adjudged appropriate for the study. Mean and standard deviation were used for data analysis while t-test statistics was used to test the hypotheses at 0.05 level of significance. It is the findings of this study that setting goals and stating procedures for their attainment are elements of system analysis that have an influence on the principals’ managerial effectiveness among others. It is therefore recommended that the principal should be proactive in exercising his systematic administrative functions for managerial effectiveness.